2019
DOI: 10.1111/plar.12305
|View full text |Cite
|
Sign up to set email alerts
|

When Biopolitics Turn Digital: Transparency, Corruption, and Erasures from the Infrastructure of Rationing in Delhi

Abstract: Following the ratification of the National Food Security Act (NFSA) in 2013, the Indian state digitized its food rationing infrastructure, replacing paper‐based ration cards with digital rationing documents and other technologies of authentication. The shift from analog to digital documentary practices has rematerialized documents and devices to enable closer monitoring of the exchange of food entitlements in ration shops. Making biopolitics digital has enabled the state to exert greater control over rationing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Such work seeks to understand how speakers use an array of semiotic modalities to co‐constitute and reproduce political economic formations in everyday life (Pigg 2001; Pinto 2004; Heritage and Clayman 2010; Gal, Kowalski, and Moore 2015). While many studies have demonstrated the importance of language for state formation and nation‐building (Ayres 2012; Anderson 1991), recent scholarship has emphasized how the state is produced through material artifacts:how forms of writing, documentation, enumeration, mapping, and more recently digitization are key semiotic technologies through which the state attains its aura of bureaucratic rationality (Hull 2003; 2012a; 2012b; V. Das 2004; Weber 2009; Mathur 2012; Gupta 2012; Mathur 2016; Carlan 2018; In Press; Dandurand 2019). Key to this process is the erasure of social actors, such that bureaucratic decisions, knowledge, and policies may be reproduced through context‐independent logics (Irvine and Gal 2000; Gal and Irvine 2019; Biruk 2018; Appel 2019; Kockelman 2016).…”
Section: Bureaucracy Collectivization Erasurementioning
confidence: 99%
“…Such work seeks to understand how speakers use an array of semiotic modalities to co‐constitute and reproduce political economic formations in everyday life (Pigg 2001; Pinto 2004; Heritage and Clayman 2010; Gal, Kowalski, and Moore 2015). While many studies have demonstrated the importance of language for state formation and nation‐building (Ayres 2012; Anderson 1991), recent scholarship has emphasized how the state is produced through material artifacts:how forms of writing, documentation, enumeration, mapping, and more recently digitization are key semiotic technologies through which the state attains its aura of bureaucratic rationality (Hull 2003; 2012a; 2012b; V. Das 2004; Weber 2009; Mathur 2012; Gupta 2012; Mathur 2016; Carlan 2018; In Press; Dandurand 2019). Key to this process is the erasure of social actors, such that bureaucratic decisions, knowledge, and policies may be reproduced through context‐independent logics (Irvine and Gal 2000; Gal and Irvine 2019; Biruk 2018; Appel 2019; Kockelman 2016).…”
Section: Bureaucracy Collectivization Erasurementioning
confidence: 99%
“…Yet where there is scope for interpretation, there is room for strategic manoeuvre. Hence there is a risk that things that are not socially legitimatable may be hidden, for instance when citizens are not able to register with a biometric system, such as Aadhaar in India, thus becoming invisible to and being made invisible by the biometricising state (Dandurand, 2019;Wevers, 2018). When such sleight of hand-even if unwittingly executed by a benevolent actor-is not detected and challenged, the effect of an impulse to quantify can be to distort what it quantifies and why.…”
Section: Ethical Dilemmas In the Societal Legitimation Of Quantificationmentioning
confidence: 99%
“…The Aadhaar example is a case in point of institutionalising non-innocent metrics. Despite clear evidence of limited data infrastructure to support reliable use of biometrics for benchmarking, and consequent risks of misdistribution in public schemes (Dandurand, 2019) or exclusion of marginalised groups like hard-working labourers with "Lost fingers, damaged fingertips, and rubbed-off skin contours" that make fingerprints unreadable (Rao, 2013, p. 74), the programme is backed by the state at the cost of vulnerable people (Drèze et al, 2017).…”
Section: Ethical Dilemmas In the Societal Legitimation Of Quantificationmentioning
confidence: 99%
“…Access (n=18) Chamuah, 2018, Chaudhuri & König, 2018, Dandurand, 2019, Drèze et al, 2017, Ghosh, 2017, Ghosh, 2018, Khera, 2017, Khera, 2018, Kotwal et al, 2017, Mir U.B et al,, 2019, Mukherjee & Sahay, 2019, Mukhopadhyay et al, 2019, Patankar, 2017, Rao, 2019, Seetharaman & Pant, 2018, Srivastava & Sharma, 2017 Abraham & Rajadhyaksha, 2015, Baxi, 2019, Bhatia & Bhabha, 2017, Chaudhuri, 2019, Jayal, 2019, Mali & Avila-Maravilla, 2018, Masiero, 2016, Masiero, 2018, Nair, 2018, Parikh, 2013, Sivamalai, 2013 Abraham, 2018, Avgerou & Addo, 2017, Cohen, 2019, Cohen, 2019, Dattani, 2019, Jayaprakash & Pillai, 2018, Masiero, 2015, Mukunthan & Agarwal, 2019, Rao, 2019, Sengupta & Shastri, 2019, Singh, 2019 Empowerment/ Emancipation (n=2) Breckenridge, 2019,Singh, 2019 Aadhaar's dual mandates of residents' enrollment and application to services through authentication (UIDAI, 2010) are oriented toward providing access through a technical-rational understanding that views the lack of (access to) a unique means of legal identification, and its associated...…”
Section: Discourse Studymentioning
confidence: 99%
“…Aadhaar is said to alter the technical terrain people must navigate to become rights-bearing citizens and adds a new layer of procedures on top of older techniques of recognition (Rao, 2019). Dandurand (Dandurand, 2019) reports that digitalization has enabled the state to exert greater control over rationing practices by rendering them more transparent but that the state's obsession with preventing practices of corruption has hindered, rather than facilitated, access to entitlements for beneficiaries.…”
Section: Participationmentioning
confidence: 99%